Efficiency evaluation of ZrB2 incorporation in the MgB 2 matrix phase using high-energy milling - Santos, Felipe Antunes; Ramos, Alfeu Saraiva [UNESP]; Dos Santos, Claudinei; Suzuki, Paulo Atsushi; Rodrigues Jr., Durval (Trans Tech Publications, 2010)
The present study suggests the use of high energy ball milling to mix (to dope) the phase MgB2 with the AlB2 crystalline structure compound, ZrB2, with the same C32 hexagonal structure than MgB 2, in different concentrations, enabling the maintenance of the crystalline phase structures practically unaffected and the efficient mixture with the dopant. The high energy ball milling was performed with different ball-to-powder ratios. The analysis of the transformation and formation of phases was accomplished by X-ray diffractometry (XRD), using the Rietveld method, and scanning electron microscopy. As the high energy ball milling reduced the crystallinity of the milled compounds, also reducing the size of the particles, the XRD analysis were influenced, and they could be used as comparative and control method of the milling. Aiming the recovery of crystallinity, homogenization and final phase formation, heat treatments were performed, enabling that crystalline phases, changed during milling, could be obtained again in the final product. © (2010) Trans Tech Publications.
Keywords: High energy ball milling; Magnesium diboride; Microstructural characterization; Scanning electron microscopy; Superconductivity; X-ray diffraction; Zirconium diboride; High-energy ball milling; Micro-structural characterization; Scanning electrons; Borides; Crystalline materials; Diffraction; Energy efficiency; High energy physics; Magnesium; Milling (machining); Milling machines; Particle size analysis; Rietveld method; Scanning; Spheres; X ray diffraction; X rays; Zirconium; Zirconium compounds; Ball milling